2011
DOI: 10.1007/s00520-010-1061-0
|View full text |Cite
|
Sign up to set email alerts
|

RANK ligand inhibition in bone metastatic cancer and risk of osteonecrosis of the jaw (ONJ): non bis in idem?

Abstract: Although the overall frequency of ONJ was low, post-marketing risk-benefit studies with this novel compound appear warranted focusing specifically on this rare toxicity, which can potentially have a high impact on quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 26 publications
4
32
1
Order By: Relevance
“…The more recent observation of ONJ in N-BP-naïve patients receiving RANKL antibodies (6-9) suggests that it may be the physiologic effect of strongly inhibiting bone resorption by any means, rather than through the specific use of an N-BP, that drives much of ONJ's pathophysiology. In this report, we show that rice rats with moderate/severe periodontitis develop ONJ-like lesions when co-administered oncologic doses of ZOL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The more recent observation of ONJ in N-BP-naïve patients receiving RANKL antibodies (6-9) suggests that it may be the physiologic effect of strongly inhibiting bone resorption by any means, rather than through the specific use of an N-BP, that drives much of ONJ's pathophysiology. In this report, we show that rice rats with moderate/severe periodontitis develop ONJ-like lesions when co-administered oncologic doses of ZOL.…”
Section: Discussionmentioning
confidence: 99%
“…(6-9) However, no cause/effect relationship has yet been established. N-BPs are powerful antiresorptive agents which bind to bone surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In fact the anti-angiogenic properties associated with BP treatment have been linked to the etiology of osteonecrosis of the jaw (ONJ), the most common side effect of BP treatment, and lower circulating VEGF levels are predictive of ONJ onset in patients receiving BP treatment (Vincenzi et al, 2012). Similar to BP treatment, ONJ has been reported in patients receiving denosumab (Smith et al, 2012), and the overall risk of ONJ was found to be slightly (but not significantly) elevated in patients receiving denosumab versus BP treatment for bone metastatic breast and prostate cancer (Van den Wyngaert et al, 2011), but the direct effects of denosumab on circulating VEGF levels in these patients have not been evaluated. Interestingly, patients receiving anti-angiogenic therapies are also at increased risk of developing ONJ (Greuter et al, 2008; Aragon-Ching et al, 2009; Christodoulou et al, 2009), likely due to angiogenic and osteogenic coupling.…”
Section: Therapeutic Potential Of Hif Targets In Bone Metastasismentioning
confidence: 99%
“…In large meta-analyses of comparative trials in metastatic breast cancer patients, within 2 years of treatment no statistically significant difference in the incidence of ONJ could be detected between denosumab (2.0% of cases) and zoledronate (1.4%) [41,55,56,57]. Among nitrogen-containing bisphosphonates, there may be a higher risk of ONJ with zoledronate compared with pamidronate or ibandronate [12].…”
Section: Side Effects Of Osteoclast Inhibitorsmentioning
confidence: 99%